Interleukin-1β in tendon injury enhances reparative gene and protein expression in mesenchymal stem cells - Koch, Drew W.; Berglund, Alix K.; Messenger, Kristen M.; Gilbertie, Jessica M.; Ellis, Ilene M.; Schnabel, Lauren V. (Frontiers in Veterinary Science, 2022)
Tendon injury in the horse carries a high morbidity and monetary burden. Despite appropriate therapy, reinjury is estimated to occur in 50 to 65% of cases. Although intralesional mesenchymal stem cell (MSC) therapy has improved tissue architecture and reinjury rates, the mechanisms by which they promote repair are still being investigated. Additionally, reevaluating our application of MSCs in tendon injury is necessary given recent evidence that suggests MSCs exposed to inflammation (deemed MSC licensing) have an enhanced reparative effect. However, applying MSC therapy in this context is limited by the inadequate quantification of the temporal cytokine profile in tendon injury which hinders our ability to administer MSCs into an environment that could potentiate their effect. Therefore, the objectives of this study were to define the temporal cytokine microenvironment in a surgically induced model of equine tendon injury using ultrafiltration probes and subsequently evaluate changes in MSC gene and protein expression following in vitro inflammatory licensing with cytokines of similar concentration as identified in vivo. In our in vivo surgically induced tendon injury model, IL-1B and IL-6 were the predominant pro-inflammatory cytokines present in tendon ultrafiltrate where a discrete peak in cytokine concentration occurred within 48 hours following injury. Thereafter, MSCs licensed in vitro with IL-1B, but not IL-6, at a concentration identified from the in vivo study induced upregulation of multiple genes beneficial to tendon healing as identified by RNA-sequencing. Specifically, vascular development, ECM synthesis and remodeling, chemokine and growth factor function alteration, and immunomodulation and tissue reparative genes were significantly upregulated. A significant increase in protein expression of IL-6, VEGF, and PGE2 was confirmed in IL-1B-licensed MSCs compared to naïve MSCs. This study improves our knowledge of the temporal tendon cytokine microenvironment following injury, which could be beneficial for the development and determining optimal timing of administration of regenerative therapies. Furthermore, these data support the need to further study the benefit of MSCs administered within the inflamed tendon microenvironment or exogenously licensed with IL-1B in vitro prior to treatment as licensed MSCs could enhance their therapeutic benefit in the healing tendon.